On a Nonlocal Boundary-Value Problem for Systems of Impulsive Hyperbolic Equations - Assanova, A. T. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We consider a nonlocal boundary-value problem for a system of impulsive hyperbolic equations. Conditions for the existence of a unique solution of the problem are established by the method of functional parameters, and an algorithm for its determination is proposed.